A Software Requirements Defect Management Approach Using Negotiation Technique To Improve Software Requirements Quality - Rosmadi, Nurul Atikah (2018)
Several defects are originated from requirements phase and poor requirements elicitation process leads to projects failure. Developing software projects with defects-free requirements are difficult, especially when project involve multiple stakeholders with different perspectives and perceptions. This is because conflicted stakeholders lead to mismatching goals and miscommunication. Traditionally, inspection method is proven effective to detect and to remove requirements defects. However, it is only feasible when the requirements document are ready. Earlier defects detection, fix and removed, can lessen the cost of testing and maintaining phase at later stages. Motivated by this, this research proposed a new defects management approach in software requirement to improve software requirements quality. This research introduces a prevention action to propose a defects management approach with embedding negotiation technique to prevent the defects from entering software requirements documents. Empirical software engineering method is adopted for this research and the evaluation is based on experimental study. A control group which deploy traditional inspection technique is used as our baseline to compare the effectiveness of defects management approach. Hence, to support that, we conduct experiments that runs both traditional and new approach using case study that involve multiple stakeholders. On top of that, five experts who are familiar with handling defects management and working in software engineering field more than five years, were selected to provide expert opinion. Overall results indicates that the new defects management approach and the inspection have similar capabilities to prevent and to detect defects respectively. Our new defect management approach able to prevent 28 percent more than inspection approach. This also means that both traditional inspection approach and the new approach complement each other by means that we can improve software requirements quality and reduce the maintenance cost in the future.